Better Work in Central America : assessing the opportunities for upgrading in Nicaragua's apparel sector /: assessing the opportunities for upgrading in Nicaragua's apparel sector. (February 2013) - Bair, Jennifer, 1973-; Gereffi, Gary
No abstract available